Project-Based Learning Via Traditional Game in Physics Learning: Its Impact on Critical Thinking, Creative Thinking, and Collaborative Skills - N. Khoiri; S. Ristanto; A. F. Kurniawan (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to investigate how PjBL via traditional games impact students’ critical thinking, creative thinking, and collaborative skills. The research sample is a local school in Semarang. The research design was a quantitative study using the pre-experimental design type one group pretest-posttest method. There is only one predetermined group in this design. The theme of the game that the project will create was revealed following the pre-test. The research results show students’ creative thinking skills in applying the PjBL model via game techniques are 61.53% in high criteria and 38.46% in medium criteria. The study results also show a fair increase in the N-Gain value for the four indicators of creative thinking skills: improvisation, elaboration, creativity, vision, effectiveness, and efficiency. The results show it is effective for six students (25%), fairly effective for 13 students (54.16%), and less effective for five students (20.83%). The study’s results also show that the Mann-Whitney U statistical test is 69. It means that the PjBL model impacts students’ collaborative skills. This research has a big impact on increasing students’ creative thinking skills and collaboration.